واقع ومعوقات إدماج التربية المتحفية في المناهج الدراسية (دراسة نوعية بمدينة أم البواقي) - زروالي, وسيلة (University of Eloued جامعة الوادي, 2021)
هدفت هذه الدراسة الى تقصي واقع ومعوقات ادماج التربية المتحفية ضمن المناهج الدراسية، اعتمدت الدراسة المنهج الكيفي باستخدام مقابلة نصف موجهة على (24) مبحوثا بمدينة أم البواقي، أظهرت نتائج تحليل محتوى المقابلات أن المتاحف في الجزائر لا تؤدي الدور التربوي والتعليمي المنوط بها كما نصت عليه الأيكوم، وأن هناك معوقات لإدماج التربية المتحفية في المناهج الدراسية أهمها: ضعف الدعم المالي، عدم التنسيق بين مختلف الهيئات والوزارات وغياب ميزانية خاصة بالزيارات الميدانية الى المتاحف، عدم وجود متاحف افتراضية داخل المؤسسات التعليمية ،عدم مساهمة وسائل الاعلام بالتعريف بالمتحف وقيمته وأثره النفسي والتربوي والوطني والحضاري. Abstract: This study aimed to investigate the reality and obstacles to integrating museum education into the school curricula. The study adopted the qualitative approach using a semi-directed interview on (24) respondents in the city of Oum El Bouaghi. The results of the interview content analysis showed that museums in Algeria do not perform the educational and educational role assigned to them as stipulated in it. AECOM, and that there are obstacles to integrating museum education in school curricula, the most important of which are: lack of financial support, lack of coordination between various bodies and ministries, the absence of a budget for field visits to museums, the absence of virtual museums within educational institutions, the lack of media participation in introducing the museum, its value and its psychological, educational and national impact And civilized.
مقال
Keywords: واقع ; معوقات ; ادماج ; التربية المتحفية ; المناهج الدراسية